THE POTENTIAL OF SPODOPTERA PECTINICORNIS IN CONTROLLING WATER LETTUCE (Pistia stratiotes) IN FIELD - Lyswiana Aphrodyanti; Helda Orbani Rosa; Samharinto Samharinto (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2017)
Spodoptera pectinicornis is a biological control agent that has a great potential to control water lettuce weeds. Its existence in nature however is still limited, so a mass propagation is needed by rearing S. pectinicornis imagoes to produce eggs and to hatch them into larvae of 4 days old. The 4-year larvae were then released by putting water lettuces that contained active larvae into the target area. Observation results on the percentage of damage in the watershed location for 5 times of observation consecutively was 25%, 50%, 50%, 75% and 90%. The magnitude of damage showed that S. pectinicornis was able to adapt well, so it could perform eating activities and cause damage to the water lettuces. Meanwhile, at the release site of rice field, the percentage of damage was 0%, 25%, 35%, 25% and 10%. The downward trend in the level of S. pectinicornis attacks was due to its inability to keep pace with the growth and development of water lettuces. High level of rainfall caused the water lettuces to increase its size and the number of its tillers so that they could colonize these waters. The fact that S. pectinicornis still has the ability to destroy the water lettuces gives great hope to the control efforts. However, thorough evaluation and assessment are required on all aspects, such as the biological control agents, weed targets, organisms associated with them, and the state of the environment so as to minimize the possibility of failure in the field.